التأسيس الأيديولوجي لمكانة المرأة في التوراة والفكر اليهودي (نساء الأنبياء انموذجاً) - بدر عبدالله شيماء (Journal of College of Education, 2020)
This research deals with the status of women in the Bible and Jewish thought and ideological foundations, and because there are many stories received about women, so we limited to the women of the prophets as a model to show that status, in addition to mention their daughters and mothers in an attempt to shed light on what the Jewish thought based on the abuse of the prophets in many The texts of the Torah, but hardly the history of a prophet from the prophets of direct exposure to such abuses that took many forms and forms, and perhaps the abuse of their women is one of them, and provide a distorted image of women in the house of the Prophet and presented as a harlot and adulterous and worshipers of idols and other, which reflected the status of women in the Jewish community .